The use of biblical themes in the debate concerning the xenophobic attacks in South Africa - Dube, Zorodzai (Verbum et ecclesia, 2015)
The study draws from the ideas of J rgen Habermas, Daniel Trotter and Christian Fuchs, Zizi Papacharissis, Yochai Benkler and Christian Fuchs to investigate the use of social media as a platform to express ideas against xenophobic-related attacks in South Africa (April 2015 May 2015). The data was collected from twitter, YouTube and Facebook. Most views came from the Facebook platform called Stop xenophobia . Using ATLAS.ti, software for qualitative research, the data was coded into interpretive variables or categories. The results show that themes such as hospitality, morality, creation and ethics received highest frequency as reasons to condemn xenophobia. The research further reveals that the social media data is much candid in comparison to state controlled media, where views and ideas were censored to protect the economic and public image of the country. Unlike the controlled government outlets which focus on the possible correlation between xenophobic attacks to economic outlook, the social media focuses on moral and ethical issues issues that define our collective as human beings and tackles xenophobia from the perspective of ethics and shared human values.Intradisciplinary and/or interdisciplinary implications: This study is interdisciplinary in nature due to the use of theories in media studies and social sciences to investigate the use of biblical themes in the fight against xenophobia.